2011
DOI: 10.1021/jo102148p
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Co-crystals for the Determination of Absolute Stereochemistry: An Alternative to Salt Formation

Abstract: Access to the full text of the published version may require a subscription. Rights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…(À)-cam. Similar cases of structural resemblance in co-crystals derived from enantiopure and racemic forms of chiral substances with achiral co-crystal formers have previously been reported (Lemmerer et al, 2008;Eccles et al, 2011). In another relevant study, (S)-and (R/S)-ibuprofen were found to form almost isostructural co-crystals with nicotinamide; in that case, the (S) and (R/S) co-crystals crystallized in monoclinic (space group P2 1 ) and orthorhombic (space group Pca2 1 ) structures, respectively (Berry et al, 2008).…”
Section: Crystal Structure Of Ccr3:2supporting
confidence: 76%
“…(À)-cam. Similar cases of structural resemblance in co-crystals derived from enantiopure and racemic forms of chiral substances with achiral co-crystal formers have previously been reported (Lemmerer et al, 2008;Eccles et al, 2011). In another relevant study, (S)-and (R/S)-ibuprofen were found to form almost isostructural co-crystals with nicotinamide; in that case, the (S) and (R/S) co-crystals crystallized in monoclinic (space group P2 1 ) and orthorhombic (space group Pca2 1 ) structures, respectively (Berry et al, 2008).…”
Section: Crystal Structure Of Ccr3:2supporting
confidence: 76%
“…The interaction between a CCF and ladderane would enable the components to pack more efficiently relative to the pure ladderane. Whereas cocrystallizations are often successfully used to aide the elucidation of the structures biological molecules (22), the application of a cocrystal strategy to determine the relative configuration of a diastereomer had not been reported (23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 99%
“…To circumvent difficulties to obtain single crystals, we revisited principles of crystal engineering by employing a cocrystallization (Scheme 3). Cocrystallizations are often used to determine structures of biomolecules (e.g., proteins) (22), yet applications to parallel problems involving small molecules have been less explored, with absolute structure determinations of steroids (23,24) and, more recently, separations and structure determinations of natural products (25,26) and a bicyclobutyl being the only examples (27). Here, a cocrystallization of the second isomer with 3,5-dinitrobenzoic acid (3,5-DNBA) readily afforded single crystals that enabled the relative configuration of chiral 1b to be confirmed.…”
mentioning
confidence: 99%
“…However, there is no single definition as to what a pharmaceutical co-crystal. Multiple definitions appear in the literature, but a common definition is "a stoichiometric multicomponent system connected by non-covalent interactions where all the components present are solid under ambient conditions" [4][5][6]. As both the API and co-former in a co-crystal must be solid on their own under ambient conditions, solvates and hydrates are not classed as co-crystals.…”
Section: Pharmaceutical Co-crystalsmentioning
confidence: 99%